Indirect selection for culinary quality and minerals in beans based on genotype × environment interaction - Dalfollo Ribeiro, Nerinéia; Maria Maziero, Sandra (Revista Ciência Agronômica, 2023)
The determination of the number of experiments required to achieve high coincidence in identifying signifi cant correlations between culinary quality traits and/or mineral concentrations is unprecedented for common bean. The objectives of this study were to evaluate correlations between culinary quality traits and minerals in common bean lines considering data from individual and combined experiments; defi ne the minimum number of experiments that provide high coincidence in identifying signifi cant correlations; and identify promising traits for indirect selection. For this, seven traits related to culinary quality and the concentration of six minerals in grains of 17 common bean genotypes were evaluated. Pearson’s linear correlation analysis was performed on data obtained from four individual experiments and six combinations of experiments. Twelve of the 13 evaluated traits showed a signifi cant genotype × environment interaction eff ect, indicating that the common bean genotypes exhibited diff erences in culinary quality and mineral concentration when these were determined in diff erent experiments. Pearson’s linear correlation coeffi cients vary in signifi cance, sign, and/or magnitude for the traits analyzed in individual and combined experiments. The use of data from three experiments provides a high coincidence percentage in identifying signifi cant correlations in Pearson’s linear correlation analysis. Common bean lines with high culinary quality and greater mineral concentration can be indirectly selected based on higher L* values (grain lightness) and higher calcium concentrations.